The Use Of âVocabulous: Vocabulary Variousâ As A Media With Vss Technique To Improve Vocabulary For Seventh Graders - Lolita, Yuri (Proceeding of International Conference on Teacher Training and Education, 2016)
Vocabulary is one of the language skills that relates with word their meanings, glossaries, and some of word used in language which the students are quite familiar with and used to communicate with others. It consists of eight parts of speech which are adjective, adverb, conjuction, interjection, noun, preposition, pronoun and verb. It becomes vital element to learn and acquire language.Vocabulary mastery is needed to develop their four aspects of communication namely, listening, reading, writing and speaking. The research used Quantitative research that was Experimental design to find and measure the improvement of the vocabulary from the test result. The design of this study was one group pre-posttest design. So this study used one class to be applied with the treatment. The data for this research was collected using test and the result of the learnersâ tasks. The researcher made conclusion from the result of the test and tasks which showed the improvement of their vocabulary mastery. The findings showed that the learners have improved their vocabulary mastery after this study conducted. The score of the posttest was higher than the pretest. In the first meeting, the learners still faced the difficulty to follow the step in analyzed vocabulary with the chart in VSS, then they could follow all the steps easily in the second meeting. And, the result of the learnersâ task in the second meeting showed the improvement than the first meeting. This study concluded that this study was succesfull to improve the vocabulary through vocabulous. The researcher suggest that this media can applied in the class to engage the learners to remember than improve their vocabulary through vocabulous.Â